Assessment of Slope Stability Problems in an Open Pit Quarry; an Example from Istanbul Cebeci Region, Turkey - Er, Selman; Yılmaz, Murat; Tuğrul, Atiye; Ertin, Altay; Tokgöz, Nuray; AREL, ERSİN (Springer Int Publishing Ag, Gewerbestrasse 11, Cham, Ch-6330, Switzerland, 2015)
Rock slope stability is one of the important problems for open pit quarrying. This paper presents an instability assessment for jointed sandstone cut slopes in Cebeci Region, Istanbul, Turkey. In the quarry site, Carboniferous sandstones including diabase dykes are cropped out and these rocks are produced as aggregate. For this study, firstly, field study involving detailed discontinuity surveys were performed. Then, kinematical analyses were carried out to determine the potential failures at the quarry. According to the results of kinematic analysis, planar and wedge types of failures are expected in different parts of quarry. Based on the field studies and stability analyses of the cut slopes, optimum slope geometry and necessary support measures are suggested.
Keywords: Sandstone; Slope stability; Open pit quarry; Kinematic analysis